The Cover Stories : Interviews with 115 designers - Ishibashi, Katsutoshi; Taniguch, Masako; Kamijyo, Masahiro; Tsujimura, Tyoko; Hasegawa, Tomoyoshi (s.l. : AXIS, 2018)
Sottsass, Ettore ; Gandini, Marcello ; Spiekermann, Erik ; Vossoughi, Sohrab ; Putman, Andrée ; Nouvel, Jean ; Moggridge, Bill ; Starck, Philippe ; Hutten, Richard ; Sejima, Kazuyo & Nishizawa, Ryue ; Warwicker, John & Baker, Steve al.
AXIS THE COVER STORIES - Interviews with 115 designers" is a book that brings together in one volume a series of cover interviews spanning 20 years of the design magazine AXIS.
boek
Keywords: Yoshiaki Tsutsui